Neurodegeneration : metallostasis and proteostasis - Milardi, Danilo; Rizzarelli, E. (Cambridge : RSC Pub., 2011)
This book covers the latest developments in the understanding the pathogenesis of neurodegenerative diseases.
Includes bibliographical references and index.
Keywords: Neurodegenerative Diseases -- etiology; Proteostasis Deficiencies -- complications; Neurodegenerative Diseases -- physiopathology